2020
DOI: 10.3390/ijerph17030803
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Assessment of Two Suicide Prevention Training Programs for the Construction Industry

Abstract: As part of a suite of early intervention training and support services, Mates in Construction (MATES) provide two general awareness programs to promote mental health and suicide awareness and encourage help-offering and help-seeking in construction workers. General awareness training (GAT) is a one-hour session delivered to all construction workers on large to medium worksites, while MATES awareness training (MAT) maintains similar content but is of shorter duration and delivered informally to small workplaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 13 publications
4
52
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to evaluate a workplace suicide prevention training program tailored for use within the energy industry, despite the impact of workplace interventions on reducing the economic burden of suicide on healthcare systems [ 8 ]. Our findings are consistent with previous similar research in the construction [ 6 , 7 , 13 , 18 , 19 , 20 ] and mining industries [ 16 , 17 ], whereby suicide literacy items, and willingness to both offer and seek help, significantly increased following GAT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to evaluate a workplace suicide prevention training program tailored for use within the energy industry, despite the impact of workplace interventions on reducing the economic burden of suicide on healthcare systems [ 8 ]. Our findings are consistent with previous similar research in the construction [ 6 , 7 , 13 , 18 , 19 , 20 ] and mining industries [ 16 , 17 ], whereby suicide literacy items, and willingness to both offer and seek help, significantly increased following GAT.…”
Section: Discussionsupporting
confidence: 92%
“…Some gender differences were also seen, with females showing a greater positive change in several of the suicide awareness items and males showing greater improvement in one of the help-seeking items. These findings are important given that previous MATES evaluation studies focused on the male-dominated industries of construction and mining, both comprised of approximately 90% males [ 17 , 19 , 20 ]. In contrast, the current sample of energy workers was comprised of approximately 27% females.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since its inception, MATES has had substantial uptake in the building and construction sector and has developed an evidence-base supporting its effectiveness. Previous evaluation research has demonstrated the social validity of the program among construction workers [11], effectiveness in shifting beliefs around suicide [12,13], improvements in suicide prevention literacy, and increased intentions among workers to offer help to workmates and to seek help for themselves [13][14][15]. Research has also demonstrated the significant economic return of investing in workplace suicide prevention initiatives such as MATES [16][17][18].…”
Section: Introductionmentioning
confidence: 99%